Altruism and Reciprocity in the Long-Run - Lugón Ceruti, Alejandro (2018)
The aim of this paper is to provide a model where altruism is determined endogenously. Altruism is an attitude that influences our actions toward other people. The model presented in this paper assumes that this influence also operates in the opposite direction via reciprocity: that is, people modify their altruism based on the actions of other agents. The paper uses a dynamic setup with two agents whose incomes are random. Depending on the incomes realized, transfers are made. These transfers convey information about the level of altruism of the donors. The agents use this information to adjust their own level of altruism. If the transfer received by an agent implies that the altruism level of the other agent is higher (lower) than that of the receiver, then the latter will increase (decrease) his level of altruism. This behavior induces a stochastic process for the levels of altruism. The long level of altruism is studied using both analytic and computer simulations tools.